Preparation of Hydrophobic Nylon Fabric. Issue 1 (March 2016) - Du, Jinmei; Zhang, Lulu; Dong, Jing; Li, Ying; Xu, Changhai; Gao, Weidong
Surface roughness and surface energy are two important factors affecting the hydrophobicity of nylon fabric. In this study, nylon fabric was treated for hydrophobicity with tetrabutyltitanate (TBT) and octadecylamine (OA) which were respectively responsible for increasing surface roughness and reducing surface energy. In order to enhance the hydrophobicity, In order to further enhance hydrophobicity by increasing available reactive sites, 1, 2, 3, 4–butanetetracarboxylic acid (BTCA) was applied as a pretreatment to the nylon fabric It was found that the carboxyl content of nylon was increased by the BTCA pretreatment. SEM images showed that the TBT treatment produced small particles on nylon fabric which made surface rough. The water contact angle of nylon fabric treated with BTCA, TBT and OA was measured to be 134°, which was much greater than the water contact angle of nylon fabric treated only with OA. This indicated that the surface roughness resulting from the TBT treatment played an important role in improving hydrophobicity of the treated nylon fabric. The resistance to water penetration and the repellency of water spray of nylon fabric treated with BTCA, TBT and OA were respectively measured to be 27.64 mbar and 85 out of 100.